Urban regeneration of the industrial zone in Smederevo: Comparative analysis - Milosavljević Marko N. (Savez inženjera i tehničara Srbije, 2021)
This paper has a focus on Urban Regeneration, with the "still-active" industrial complex as the main element, on the Eastern outskirt of the City of Smederevo. It includes revitalization and networking with the cultural assets of the city, emphasizes their importance in terms of traditional and tourist conditions, in direct communication with a necessary urban methods for the revitalization of the entire area and the City of Smederevo. Due to the Comparative analysis of the "good practice" examples of the similar cities in Italy, the valorization of space and approaching the basic goal of the research has been performed. The aim of the research of this paper is to achieve the most effective urban regeneration and the new level of intervention along with the settings of guidelines for improving the quality of the completely coverage of the zone in which the complex is located, not only the certain zone of the industrial complex.